Upaya Meningkatkan Kemampuan Mengenal Anggota Tubuh Menggunakan Media Poster pada Anak Tunagrahita Ringan Kelas III di SDLBN Pembina Kupang - Selan, Ot Bil Wilson; Wangge, Vinsensius; Junita, Allini Hesti; Pelun, Avril Desi Deria M.; Talu, Theresia D.; Paus, Gregorius J.; Laiskodat, Dina Apryana K. (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The context of this research focuses on the challenges children with mild intellectual disabilities face in recognizing body parts, an important part of their cognitive and social development. For students to better understand this concept, they need effective and fun learning.The purpose of this study was to improve the body parts recognition skills of children with mild intellectual disabilities through the use of attractive and interactive poster media. The method used was classroom action research, conducted in two cycles consisting of planning, action, observation and reflection. The research subjects were third grade students with special needs, and the focus was on improving their understanding of the names and functions of body parts.The results showed that the ability to recognize body parts improved significantly after using poster media. In each cycle, data was collected through initial and final tests, as well as observations of students' learning activities. At the end of the second cycle, students' average scores increased significantly, showing the effectiveness of using poster media in learning.This study concludes that poster media can be an effective tool to improve the body part recognition skills of children with mild intellectual disabilities. It is hoped that the findings of this study can be a reference for educators who develop innovative learning methods to meet the needs of students with special needs.